The effect of foliar spraying with seaweed extract on some vegetative growth characteristics of olive tree seedlings of olive trees cv. Khodairy. - أبو الشملات, ربى (Latakia University Journal -Biological Sciences Series, 2025)
The research was carried out in the Al-Druqiyat area of ​​Latakia Governorate during the 2022/2023 seasons, with the aim of studying the effect of foliar spraying with seaweed extract on the growth of olive seedlings of the Al-Khodairi variety. The spraying process was carried out with the extract (yam yam100) at a concentration of 0.75 g/l according to the following parameters: T0: control without spraying, T1: one spray in the month of March, T2: two sprays in the month of March and May, T3: three sprays in the month of March, May and July, with Add organic ground fertilizer. The experiment was designed in a completely randomized with four replications for each treatment. The results of foliar spraying showed a positive effect on vegetative growth characteristics. The spray treatments were significantly superior to the average length of shoots, the increase in stem diameter, and the height of the planter over the control, which achieved the lowest values ​​(9.5 cm, 1.53 mm, and 16.33 cm), respectively, while the spray treatment with marine algae extract exceeded T3 three times in average leaf area and leaves content of Total chlorophyll and dry matter percentage were significantly different from the rest of the experimental treatments (5.05 cm, 2.33 mg/g, 51.21%).